2002
DOI: 10.1530/rep.0.1230355
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and biological roles of oviduct-specific, oestrogen-dependent glycoprotein

Abstract: During late follicular growth, oestrus, fertilization and early embryonic development, the oviduct, under specific hormonal control, produces fluid and contributes secretory macromolecules that optimize the microenvironment for gamete maturation and transport, fertilization and early cleavage-stage embryonic development. This review describes the state of knowledge concerning the physiological and biochemical characterization of the major oviduct secreted protein, the oviduct-specific, oestrogen-dependent glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(158 citation statements)
references
References 10 publications
3
153
0
2
Order By: Relevance
“…We analyzed the localization of DMBT1 in different sections of porcine oviduct (ampulla and isthmus) during the different estrous cycle stages. In both regions, the immunostaining was present mainly in non-ciliated cells, which are secretory cells mainly involved in the synthesis and release of glycoproteins that dissolve in the oviductal fluid (Buhi 2002, Abe & Hoshi 2007, Desantis et al 2011, but also in other cell types. The secretion of DMBT1 seems to follow the stages of the estrus cycle, as the presence of the protein is observed from the end of follicular phase in both isthmus and ampulla.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the localization of DMBT1 in different sections of porcine oviduct (ampulla and isthmus) during the different estrous cycle stages. In both regions, the immunostaining was present mainly in non-ciliated cells, which are secretory cells mainly involved in the synthesis and release of glycoproteins that dissolve in the oviductal fluid (Buhi 2002, Abe & Hoshi 2007, Desantis et al 2011, but also in other cell types. The secretion of DMBT1 seems to follow the stages of the estrus cycle, as the presence of the protein is observed from the end of follicular phase in both isthmus and ampulla.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some oviductal proteins have been shown to interact with gametes and to improve efficiency of IVF in porcine (McCauley et al 2003, bovine (Martus et al 1998), human (O' Day-Bowman et al 1996), and equine (Mugnier et al 2009) species. Some of these proteins, such as osteopontin, have been identified (Hao et al 2006, Goncalves et al 2008, Monaco et al 2009) in cattle and pigs and atrial natriuretic peptide A (Anderson et al 1994, Zamir et al 1995, Zhang et al 2006 and oviductin (oviduct-specific glycoprotein; Martus et al 1998, Buhi 2002, McCauley et al 2003 in cattle, pigs, and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Part of the complex mixture of proteins that are present in the oviductal fluid come from serum transudate, but there are also specific proteins synthesized and secreted by the oviductal epithelium, and some of them could be regulated by cyclic hormonal changes, with increased biosynthesis at the periovulatory period , Buhi 2002.…”
Section: Reproduction (2015) 149 R1-r14mentioning
confidence: 99%
“…The production and secretion of high-molecular-weight (MW 70-130 kDa) glycoproteins from the oviductal epithelium seem to be associated with hormonal changes during the ovulatory cycle in different species , Buhi 2002, Leese et al 2008, AvilĂ©s et al 2010. Oviductins, also known as oviduct-specific glycoproteins, have been found in the oviducts of every mammalian species studied to date, and the cDNA sequences for these glycoproteins indicated that they show a high homology among species (Donnelly et al 1991, Arias et al 1994, Buhi et al 1996.…”
Section: Oviductinsmentioning
confidence: 99%
See 1 more Smart Citation